Neurokinin-1 receptor expression in inflammatory bowel disease: molecular quantitation and localisation - Goode, T (2000)
BACKGROUND—Substantial evidence implicates the neuropeptide substance P (SP) in mucosal immunoinflammatory responses. Autoradiographic studies have suggested a disturbance in SP receptor expression in inflammatory bowel disease (IBD). AIMS—Because of technical limitations such as poor cellular resolution with autoradiography, we used molecular methods to specifically localise the cellular expression of the neurokinin-1 receptor (NK-1R) in IBD colon, and to quantitate NK-1R mRNA expression levels therein. METHODS—In situ hybridisation and immunohistochemistry were used to localise NK-1R mRNA and protein, respectively, in normal, ulcerative colitis (UC), and Crohn's disease (CD) colonic resections. NK-1R mRNA expression levels of normal, UC, and CD mucosal biopsies were quantitated by competitive reverse transcription-polymerase chain reaction. RESULTS—NK-1R expression was localised to lamina propria mononuclear cells, epithelium, submucosal vasculature, smooth muscle, and myenteric plexus of normal and IBD colon. No ectopic NK-1R expression was observed in IBD. However, we found increased numbers of NK-1R expressing lymphoid cells in IBD tissue, aberrant negative epithelial expression of NK-1R in UC, and increased expression of NK-1R in CD myenteric plexus. Quantitation of NK-1R mRNA expression in IBD colonic mucosal biopsies revealed marked upregulation of NK-1R mRNA levels compared with non-inflamed mucosal expression levels (p<0.01). CONCLUSIONS—This report demonstrates the strategic localisation and upregulation of NK-1R expression in IBD colon, and thereby suggests the involvement of substance P in the pathophysiological symptoms of IBD.   Keywords: substance P; neurokinin-1 receptor; inflammatory bowel disease